2016
DOI: 10.3389/fphar.2016.00186
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*58:01 for Allopurinol-Induced Cutaneous Adverse Drug Reactions: Implication for Clinical Interpretation in Thailand

Abstract: Background: The aim of this study was to investigate the predisposition to different types of allopurinol-induced cutaneous adverse drug reactions (CADR), including Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN; SJS-TEN, n = 13), drug reaction with eosinophilia and systemic symptoms (DRESS, n = 10) and Maculopapular eruption (MPE; n = 7), conferred by HLA-B*58:01 in a Thai population.Methods: This case-control association study compares 30 patients with allopurinol-induced CADR, allopurinol-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 31 publications
4
35
0
3
Order By: Relevance
“…Association of HLA-A 31:01 with carbamazepine – induced SJS have been reported in children [60]. A study in Thailand concluded that there is an association between HLAB (*) 58:01 and allopurinol-induced SJS-TEN in a Thai population [61]. Similar findings were obtained in Korean cases [62].…”
Section: Discussionmentioning
confidence: 57%
“…Association of HLA-A 31:01 with carbamazepine – induced SJS have been reported in children [60]. A study in Thailand concluded that there is an association between HLAB (*) 58:01 and allopurinol-induced SJS-TEN in a Thai population [61]. Similar findings were obtained in Korean cases [62].…”
Section: Discussionmentioning
confidence: 57%
“…These patients were admitted to the hospital for treatment of CTX-induced SCARs between 2014 and 2017 and were prospectively enrolled in our study. The patients recruited in the present study are different from those previously reported by Kongpan et al 13 The RegiSCAR criteria were used to diagnose and classify SCARs, 18,19 and a dermatologist and allergist confirmed the diagnoses based on the photographs, pathological slides, clinical morphology, and medical records. SJS was defined as a mucocutaneous disorder characterized by skin rash and skin detachment affecting < 10% of the body surface area.…”
Section: Patient Recruitmentmentioning
confidence: 85%
“…HLA-DQB1, human leukocyte antigen-DQB1; AF, allele frequency; CF, carrier frequency; HW, Hardy-Weinberg equilibrium; Significantly different p-value < 0.05. (Cristallo et al, 2011;Sukasem et al, 2014;Su et al, 2016;Sukasem et al, 2016) HLA-C*03:02 SJS/TEN 7.77 7.50 6.00 10.00 9.00 5.71 0.7394 (Cristallo et al, 2011;Li et al, (Chantarangsu et al, 2009;Sukasem et (Continued) ( Tables 7, 8A). Moreover, co-trimoxazole-induced SJS/TEN associated with HLA-B*15:02 (7.66%) and -C*08:01 (10.32%) alleles was higher within Thai population than that of African Americans, Caucasians, Hispanics, and North American.…”
Section: Distribution Of Pharmacogenetics Markersmentioning
confidence: 99%